Tim-3 Blockade Elicits Potent Anti-Multiple Myeloma Immunity of Natural Killer Cells - Jiang, Wen; Li, Fanglin; Jiang, Yang; Li, Shengli; Liu, Xiaoli; Xu, Yaqi; Li, Binggen; Feng, Xiaoli; Zheng, Chengyun (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is still an incurable plasma cell tumor Natural killer (NK) cells are characterized by efficient anti-tumor activity, and their activity is one of the basis of cancer immunotherapeutic strategies. Tim-3, one of the immune checkpoint molecules, negatively regulates NK cell activity. In order to evaluate roles of Tim-3 pathway blocking in the regulation of NK cell mediated- anti-MM activity in vitro and in vivo, anti-Tim-3 and/or anti-its ligand (HMGB1, CEACAM1 or Galetin-9) antibodies were applied respectively to block Tim-3 pathway in our present study. Our results showed that Tim-3 was highly expressed on NK cells, in particular on in vitro expanded NK (exNK) cells. NK cells with Tim-3 blockade displayed a significantly higher degranulation and cytolytic activity against both human MM cell lines and primary MM cells, respectively, when compared to the isotype control antibody treated NK cells. The increased NK cell cytolytic activity by Tim-3 blocking was associated with up-regulation of cytotoxicity-related molecules, such as perforin, granzyme B, TNF-α and IFN-γ. As observed, ligand (HMGB1, CEACAM1 or Galetin-9) expression on MM cells were at different levels, and accordingly, the improvement in NK cell-mediated killing activity by different ligand blocking were also varying. Comparatively, Tim-3 blocking showed much more efficient enhancement of NK cell cytolytic activity than its ligand blockings. More importantly, exNK cells with Tim-3 blockade significantly inhibited MM tumor growth and prolonged the survival of MM-bearing NOD/SCID mice. Our results also showed that NK cells from peripheral blood and bone marrow of MM patients expressed much higher level of Tim-3 than controls. Taken our findings together, we may speculate that Tim-3 could be an important target molecule used for developing an antibody and/or NK cell based immunotherapeutic strategies for MM.